2016
DOI: 10.29252/jnkums.7.4.829
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the goiter and thyroid dysfunction in healthy children aged 7-18 years in Bojnurd in 2011

Abstract: Background and Objectives: Enlargement of the thyroid gland is called goiter. The aim of this study is to investigate the prevalence of the goiter and thyroid dysfunction in healthy children aged 7-18 years in Bojnurd city. Materials & Methods: This cross-sectional study was carried out on 176,7-18 years old students in Bojnurd. The demographic and anthropometric data were collected with questionnaires. Physical examination was performed by endocrinologist in order to staging of goiter. Fasting blood sample wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After full text review of 219 articles, 18 papers with a sample size of 42,793 subjects were found to be eligible for systematic review according to inclusion and exclusion criteria [4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (Fig. 1); based on the results of systematic review, six studies were related to the prevalence of hyperthyroidism in general population without age restriction (category 1) [4,16,18,19,27,28], four studies assessed the prevalence of hyperthyroidism in <20 years old population (category 2) [17,20,21,30], five studies reported the prevalence of hyperthyroidism in subjects with goiter (category 3) [4,17,23,28,29], three studies reported the incidence rate of hyperthyroidism (category 4) [16,22,31], and seven studies reported the diagnostic, medical treatment, or drug-prescription rate of overt hyperthyroidism (category 5) [4,15,16,18,[24][25][26]<...>…”
Section: Characteristic Of the Studies Includedmentioning
confidence: 99%
“…After full text review of 219 articles, 18 papers with a sample size of 42,793 subjects were found to be eligible for systematic review according to inclusion and exclusion criteria [4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (Fig. 1); based on the results of systematic review, six studies were related to the prevalence of hyperthyroidism in general population without age restriction (category 1) [4,16,18,19,27,28], four studies assessed the prevalence of hyperthyroidism in <20 years old population (category 2) [17,20,21,30], five studies reported the prevalence of hyperthyroidism in subjects with goiter (category 3) [4,17,23,28,29], three studies reported the incidence rate of hyperthyroidism (category 4) [16,22,31], and seven studies reported the diagnostic, medical treatment, or drug-prescription rate of overt hyperthyroidism (category 5) [4,15,16,18,[24][25][26]<...>…”
Section: Characteristic Of the Studies Includedmentioning
confidence: 99%